Responses to vaccination in strains of mice that differ in susceptibility to coccidiosis. - Rose, M E (1996)
BALB/c mice are normally resistant to infection with Eimeria vermiformis than C57BL/6 (B6) mice, but these phenotypes were reversed by prior vaccination with crude antigens prepared from developmental stages of the parasite: B6 mice were protected, and BALB/c mice were made more susceptible. Infections with a heterologous species, E. pragensis, were unaffected when this was given either alone or together with E. vermiformis. In both strains of mice, vaccination induced serum antibody responses to E. vermiformis and the levels were boosted by superimposed infection, the highest values being found in BALB/c mice. Cellular responses in the mesenteric lymph nodes (MLN), as indicated by cellularity and proliferation, either unstimulated or restimulated in vitro with E. vermiformis antigen, were decreased in both strains, but markedly more in BALB/c than B6. The capacity of MLN cells to transfer immunity to naive recipients was lowered by vaccination of BALB/c donors but unimpaired in vaccinated B6 mice. Responses to the mitogen, concanavalin A, and to unrelated antigens (human erythrocytes and fowl gamma globulin) were unaffected. Thus, parenteral vaccination, which increased the susceptibility of BALB/c mice to infection with E. vermiformis, had a depressing effect on some specific immune responses in the MLN. It was surprising to find some reduction in the cellular responses of the MLN of B6 mice also, although they were protected by vaccination.